2020
DOI: 10.1097/mol.0000000000000682
|View full text |Cite
|
Sign up to set email alerts
|

Remnant lipoproteins: are they equal to or more atherogenic than LDL?

Abstract: Purpose of review To critically appraise new insights into the biology of remnant lipoproteins and their putative role in the pathophysiology of atherosclerotic cardiovascular disease, and to compare the atherogenicity of remnant particles with that of LDL. Recent findings New in vivo stable isotope tracer studies of the kinetics of apoB48-and apoB100-containing lipoproteins in postprandial conditions have revealed that apoB48-containing VLDL accumulated markedly in hypertriglyceridemic subjects. These intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Furthermore, our study found that MetS mediated the association between RC and new-onset CVD. In recent years, RC had attracted a lot of attention as a residual cardiovascular risk factor in many large cohort studies, and was highly instrumental due to its great atherogenic capacity [41,42]. Unlike LDL-C, RC is free to enter the intima and become trapped in the connective tissue matrix, and could also be taken up by macrophages without modi cation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study found that MetS mediated the association between RC and new-onset CVD. In recent years, RC had attracted a lot of attention as a residual cardiovascular risk factor in many large cohort studies, and was highly instrumental due to its great atherogenic capacity [41,42]. Unlike LDL-C, RC is free to enter the intima and become trapped in the connective tissue matrix, and could also be taken up by macrophages without modi cation.…”
Section: Discussionmentioning
confidence: 99%
“…RLP-C is defined as the cholesterol content in TG-rich lipoproteins (TRLs), namely intermediate-density lipoprotein (IDL), very low-density lipoprotein (VLDL), and chylomicron remnants [ 47 49 ]. As TG contents are gradually degraded by lipoprotein lipase in the bloodstream, the cholesterol in RLP-C could also be involved in atherosclerosis plaque formation and subsequent cardiovascular events, and it has been recognized as more atherogenic and proinflammatory than the cholesterol in LDL-C [ 48 52 ]. A recent study indicated associations of plasma TGs and relatively small-sized LDL particles with the carotid-femoral PWV, despite no significant associations between VLDL/large IDL subclasses (the main carriers of TG in the blood) and the carotid-femoral PWV [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol carried by TGRLs and their remnants is a causal factor of ASCVD except for LDL-C. The structural characteristics of TGRLs and their remnants, such as lipid content, apolipoprotein components, particle size, and retention time in circulation, determine the burden of atherosclerosis ( Aguilar Salinas and John Chapman, 2020 ; Packard et al, 2020 ; Duran and Pradhan, 2021 ). Although there are several available methods for quantification of TGRLs and their remnants, more specific methods are needed to accurately determine and quantify the subclasses of these particles that are derived from different metabolic pathways.…”
Section: Future Directionsmentioning
confidence: 99%